Exposure to Family and Friend Homicide in a Nationally Representative Sample of Youth. Issue 7 (April 2021) - Turner, Heather A.; Finkelhor, David; Henly, Megan
This study examines the lifetime prevalence and distribution of family/friend homicide exposure among children and adolescents age 2 to 17 in the United States, and assesses the impact of family/friend homicide on emotional and behavioral outcomes, while controlling for potential co-occurring factors. Data were collected by telephone about the experiences of youth in 2008, 2011, or 2014, as part of the National Surveys of Children's Exposure to Violence (NatSCEV). Analyses are based on a pooled sample ( n =11, 771) from these three surveys. Approximately 8% of all children and youth ages 2 to 17 were exposed to a family/friend homicide. Older adolescents, Black youth, those living in single parent and nonparent family households, those from lower socioeconomic status households, and youth living in large cities were overrepresented among youth experiencing family or friend homicide. Exposed youth were also substantially more likely to be poly-victims, experience other major adversities, and live in neighborhoods with more community disorder. Exposure to family/friend homicide was significantly related to trauma symptoms. However, when other co-occurring factors were taken into account, only family/friend homicide that occurred within the last 2 years remained significant. With respect to delinquency, only nonfamily homicide exposure remained significant with these other factors controlled. Findings suggest that family/friend homicide represents a powerful marker for a broad level of victimization risk and adversity, demonstrating that family/friend murder is often just one relatively small part of a more complicated life of adversity. Although recent exposure is certainly distressing to youth, it is the wider, co-occurring context of poly-victimization and other types of adversity that appears most impactful in the longer term.